Shank2 Deletion in Parvalbumin Neurons Leads to Moderate Hyperactivity, Enhanced Self-Grooming and Suppressed Seizure Susceptibility in Mice - Lee, Seungjoon; Lee, Eunee; Kim, Ryunhee; Kim, Jihye; Lee, Suho; Park, Haram; Yang, Esther; Kim, Hyun; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2018)
Shank2 is an abundant postsynaptic scaffolding protein implicated in neurodevelopmental and psychiatric disorders, including autism spectrum disorders. Deletion of Shank2 in mice has been shown to induce social deficits, repetitive behaviors, and hyperactivity, but the identity of the cell types that contribute to these phenotypes has remained unclear. Here, we report a conditional mouse line with a Shank2 deletion restricted to parvalbumin (PV)-positive neurons (Pv-Cre;Shank2fl/fl mice). These mice display moderate hyperactivity in both novel and familiar environments and enhanced self-grooming in novel, but not familiar, environments. In contrast, they showed normal levels of social interaction, anxiety-like behavior, and learning and memory. Basal brain rhythms in Pv-Cre;Shank2fl/fl mice, measured by electroencephalography, were normal, but susceptibility to pentylenetetrazole-induced seizures was decreased. These results suggest that Shank2 deletion in PV-positive neurons leads to hyperactivity, enhanced self-grooming, and suppressed brain excitation.